Randomized Phase II Trial to Compare the Efficacy of Haloperidol and Olanzapine in the Control of Chemotherapy-Induced Nausea and Vomiting in Nepal - Soniya Dulal; Bishnu Dutta Paudel; Prakash Neupane; Aarati Shah; Bibek Acharya; Bishesh Sharma Poudyal; Ramila Shilpakar; Lori Wood (2019)
PURPOSE The purpose of the study was to compare efficacy and toxicity of olanzapine (OLN; a higher-cost drug) and haloperidol (HAL; a lower-cost drug) in the prevention of chemotherapy-induced nausea and vomiting (CINV) in patients who receive highly emetogenic chemotherapy (HEC). PATIENTS AND METHODS In a randomized, phase II trial, patients were randomly assigned to receive either OLN 10 mg orally on days 1 to 4 or HAL 1 mg orally on day 1 and 0.5 mg twice daily on days 2 to 4. Both groups received ondansetron 16 mg and dexamethasone 12 mg intravenously on day 1. Patients recorded their nausea using the Edmonton Symptom Assessment Scale (ESAS) and recorded daily episodes of vomiting from day 1 to day 5. The primary end point was complete nausea prevention (CNP; ie, ESAS of 0). Secondary end point was complete emesis prevention (CEP). RESULTS Sixty-five patients were randomly assigned, and 64 received their allocated treatment (n = 32 in each arm). There was no difference in CNP during the overall period (days 1 to 5) between OLN and HAL (68.7% v 71.8%; P = .78). In the acute period (day 1) and the delayed period (days 2 to 5), CNP was similar between OLN and HAL (acute: 84.3% v 81.2%; delayed: 68.7% v 75%). No difference was identified in the rate of CEP during the overall period (81.2% with OLN v 78.1% with HAL; P = .75), during the acute period (93.7% with OLN v 90.6% with HAL), or during the delayed period (84.3% with OLN v 84.3% with HAL). No difference in toxicities was noted between treatment arms. CONCLUSION In this study, HAL had comparable efficacy to OLN in the management of CINV, which suggests that it is the higher-value option in patients who receive HEC in resource-scarce countries.